Heyndrickxia coagulans SANK70258 supplementation improves growth performance, gut health, and liver function in growing pigs - Aida, Masanori; Yamada, Ryouichi; Kawase, Takahiro; Matsuo, Toshiki; Tsukahara, Takamitsu (Frontiers in Veterinary Science, 2025)
Heyndrickxia coagulans is a Gram-positive, facultatively anaerobic, and spore forming bacterium. This species is often used as probiotics, therefore it is known for its health-conferring effects on livestock and humans. Previously, we showed that administering H. coagulans SANK70258 (SANK70258) to coccidiosis-infested broilers improved their growth performance by inducing anti-inflammation. Nonetheless, a few studies have observed the effects not only of H. coagulans spp. but also of SANK70258 in pigs. Here, we evaluated if SANK70258 could help improve the growth of pigs from weaning (days 0–42), growing (days 42–84) to fattening (days 84–126) periods. Twenty-four weaned crossbred (Duroc × Large White × Landrace) piglets were divided into control (CC; 4 replicants, n = 8) and 0.01% SANK70258 supplementation (P; 8 replicants, n = 16) groups. Diets and water were given ad libitum. After the weaning period (day 42), the pigs in group P were further sub-divided into pens with (PP; 4 replicants, n = 8) or without SANK70258 administration (PC; 4 replicants, n = 8). SANK70258 improved growth performance during the growing period [statistical differences were observed on days 42–56 (PP) and 70–84 (PP and PC)]. During weaning, a period well recognized as a frequent pathogen infection stage, due to the portal blood of pigs with leaky guts flows into the liver carrying gut microbes and their products such as endotoxin and bacterial DNA. P pigs experienced an improved liver function evidenced by the plasma alanine aminotransferase reduction and hence, a putative improved leaky gut condition evidenced by the plasma lactulose/mannitol ratio reduction. Nonetheless, during the fattening period, the positive effects became confounding with a pathogenic infection expressing a drastic increase in plasma aspartate aminotransferase on day 126. Nonetheless, stearate composition in meat of PP pigs were observed on day 126. Our results suggested that the SANK70258 administration may be a good natural product to improve the growth performance of pigs during production stages with a lower probability of infection like the growing period.